Rancang Bangun Mesin Pembuat Pellet Berbais Internet Of Things (IOT) Untuk Mengotomatisasi Produksi Pakan - Hairil Novansyah, Yogi Isro Mukti, Riduan Syahri (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya Lubuklinggau, 2021)
This study aims to build an Internet Of Things (IOT)-based pelletizing machine to automate the production of poultry feed, in order to save time and save costs with the machine. In this study, farmers still buy pur/pellets so that feed on ducks is more expensive than making their own, while with Pagar Alam conditions which have agriculture such as rice fields and extensive plantations there are many materials that can be processed such as bran, milled corn, fish meal and Tofu pulp is very good for duck feed, therefore it is necessary to make a poultry feed making machine. In making duck feed, you can use the Internet of Things (IOT), the advantage of using the Internet of Things (IOT) is to simplify and speed up operations. The mixer is used as a mixer for the dough ingredients and a mill for the dough maker, the water pump acts as a driver, the relay functions as a breaker and an electric current connector, the NodeMCU ESP8266 is programmed to disconnect and connect the electric current, using the blynk application. In this study using the Raqid Application Development (RAD) development method using Expert Review testing to test the validity. To obtain data in this study, data collection techniques were carried out including observation, interviews, literature studies and questionnaires. The results of this study resulted in the automation of poultry feed production so as to save time and save costs using an Internet Of Things (IOT)-based pellet making machine. Comparison of the manual mixing and manufacturing process with the automation of poultry feed production, which is 1 kg, it takes 6.40 minutes, while the automation only takes 2 minutes, can be seen in table 4.12. and test the validity of all very valid questions.